16s rRNA gene sequencing and radioisotopic analysis reveal the composition of ammonia acclimatized methanogenic consortia. (January 2019) - Tian, Hailin; Treu, Laura; Konstantopoulos, Konstantinos; Fotidis, Ioannis A.; Angelidaki, Irini
Graphical abstract: Highlights: Acclimatization of methanogenic consortia to extreme ammonia levels. Methanomassiliicoccus luminyensis consumes acetate to produce biomass but not CH4 . Strict methylotrophic M. luminyensis was dominant at 37 °C in acetate-fed reactors. Aceticlastic pathway was dominant at extreme ammonia levels. Methanosarcina spp. ( M. thermophila & M. soligelidi ) were vital at high FAN levels. Abstract: Different mesophilic and thermophilic methanogenic consortia were acclimatised and enriched to extreme total ammonia (9.0 and 5.0 g NH4 + -N L −1, respectively) and free ammonia (1.0 and 1.4 g NH3 -N L −1, respectively) levels in this study. [2- 14 C] acetate radioisotopic analyses showed the dominance of aceticlastic methanogenesis in all enriched consortia. According to 16S rRNA gene sequencing result, in mesophilic consortia, methylotrophic Methanomassiliicoccus luminyensis was predominant, followed by aceticlastic Methanosarcina soligelidi . A possible scenario explaining the dominance of M. luminyensis includes the use of methylamine produced by Tissierella spp. and biomass build-up by metabolizing acetate. Nevertheless, further studies are needed to pinpoint the exact metabolic pathway of M. luminyensis . In thermophilic consortia, aceticlastic Methanosarcina thermophila was the sole dominant methanogen. Overall, results derived from this study demonstrated the efficient biomethanation ability of these ammonia-tolerant methanogenic consortia, indicating a potential application of these consortia to solve ammonia toxicity problems in future full-scale reactors.